High uniformity synthetic quartz ingot for semiconductor lithography reticle and chemical vapor deposition apparatus therefor
Patent Information
- Application Number
- CN202611080598.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]本发明的目的在于,克服现有技术中存在的缺陷,提供一种用于半导体光刻透视镜的高均匀性合成石英锭及其化学气相沉积装置,旨在解决现有技术中石英锭折射率均匀性不足、沉积过程温控精度低、尺寸受限等技术问题,实现折射率均匀性δn≤1×10-6、双折射≤3nm/cm、直径≥600mm的高均匀性合成石英锭的稳定制备
折射率均匀性显著提升:通过独立温控的盘形埚底和环形气幕隔离技术,将沉积靶面温度梯度控制在5℃以内,结合实时反馈调节,使石英锭折射率均匀性达到δn≤1×10-6,优于现有技术(δn≈2×10-6)。
Smart Images

Figure CN123003124A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical materials and their preparation technology for semiconductor manufacturing, specifically to a highly uniform synthetic quartz ingot for semiconductor lithography lenses and its chemical vapor deposition apparatus. This invention belongs to the field of integrated circuit manufacturing, particularly to the technology of core optical materials and their preparation equipment for lithography machines used in the manufacturing of semiconductor device-specific equipment. Background Technology
[0002] As the process nodes of large-scale integrated circuits continue to shrink, photolithography technology has evolved from 248nm KrF excimer lasers to 193nm ArF excimer lasers, and is continuing to evolve towards even shorter wavelengths. The projection optics system, illumination optics system, and mask substrate of the photolithography apparatus place extremely high demands on optical materials: the refractive index uniformity δn must be better than 2×10⁻⁶. -6 It has a birefringence of less than 5 nm / cm and excellent resistance to laser damage.
[0003] Synthetic quartz glass has become a core material for deep ultraviolet lithography optical systems due to its excellent optical transmittance, low coefficient of thermal expansion, and chemical stability. However, large-size quartz ingots prepared by existing vertical CVD methods generally suffer from problems such as uneven refractive index distribution, striation defects, and stress concentration, which seriously restrict further improvement in lithography resolution.
[0004] In existing vertical CVD processes, silicon-containing raw materials are hydrolyzed in an oxyhydrogen flame to generate SiO2 particles, which are then deposited onto a rotating target to form a quartz ingot. Patent CN117776505A discloses a large-size synthetic quartz glass ingot deposition furnace that employs a detachable rotating and lifting crucible to improve gas flow stability. However, this method suffers from difficulty in precisely controlling the distance between the target surface and the burner during deposition, leading to fluctuations in the deposition temperature field and affecting the refractive index uniformity of the quartz ingot.
[0005] The paper "Study on the Structural Uniformity of CVD Synthetic Quartz Glass" published by Sui Mei et al. in the *Journal of Wuhan University of Technology*, 2010, 32(22):106-110, found that quartz glass produced by vertical processing exhibits a layered structure distribution perpendicular to the deposition surface, with each layer approximately 0.16 cm thick, leading to a periodic distribution of structural stress. The paper "Current Status of Domestic and International Development of Simulation of Airflow Field in Synthetic Quartz Glass Furnace" published by Zhou Jianxin, Nie Lanjian et al. in the *Bulletin of the Chinese Ceramic Society*, 2024, 43(4):1230-1236, pointed out that the stability of the airflow field in the furnace is a key factor in improving the production efficiency and quality of synthetic quartz glass. These studies indicate that the structural uniformity of CVD synthetic quartz glass is mainly determined by the temperature field and airflow field distribution during the deposition process.
[0006] To address the challenges of quartz ingot forming in traditional methods, existing technologies employ crucible supports for deposition. However, patents with publication numbers CN118993508A and CN118954913B both face the problem of crucible size limiting the ingot height, making it difficult to meet the quartz ingot size requirements of large-size photolithography lenses. Huang Yaosong's paper, "Formation and optimization of deposition surface shape during fused silica glass synthesis by chemical vapor deposition," published in the International Journal of Applied Glass Sciences, 2019, DOI: 10.1111 / ijag.14771, uses numerical simulations to demonstrate that the deposition surface shape has a decisive influence on the internal temperature distribution of quartz glass; both convex and concave deposition surfaces generate significant temperature gradients on the glass's sides.
[0007] Nikon Corporation's series of patents, such as those with publication numbers CN1657456A and CN1226212C, focus on hydrogen molecule doping and ultraviolet absorption coefficient control in quartz glass. However, the improvement of refractive index uniformity mainly relies on subsequent heat treatment methods and fails to solve the uniformity problem from the deposition source.
[0008] In summary, the existing technology has the following pressing technical problems that need to be solved: the refractive index uniformity of quartz ingots is difficult to meet the requirements of advanced photolithography, i.e., δn≤2×10 -6 The unstable temperature and gas flow fields during CVD deposition lead to streaks and stress defects; crucible deposition is limited in size, making it impossible to prepare large-sized, highly uniform quartz ingots; and there is a lack of systematic solutions to simultaneously optimize the intrinsic uniformity of quartz ingots and control the deposition process. Summary of the Invention
[0009] The purpose of this invention is to overcome the deficiencies in the prior art and provide a highly uniform synthetic quartz ingot for semiconductor lithography lenses and its chemical vapor deposition apparatus. This aims to solve technical problems in the prior art such as insufficient refractive index uniformity of quartz ingots, low temperature control accuracy during deposition, and size limitations, achieving a refractive index uniformity δn ≤ 1 × 10⁻⁶. -6 Stable preparation of highly uniform synthetic quartz ingots with birefringence ≤3nm / cm and diameter ≥600mm.
[0010] To achieve the above objectives, the technical solution of this invention is to design a highly uniform synthetic quartz ingot for semiconductor photolithography lenses. The synthetic quartz ingot is prepared by chemical vapor deposition and has the following performance indicators: refractive index uniformity δn ≤ 0.9 × 10⁻⁶. -6The test wavelength was 633nm, and the measurement was performed using an interferometer according to ISO 10110-14. Birefringence ≤2.5nm / cm, test wavelength 633nm; Initial absorption coefficient at 193 nm ≤ 0.0012 cm⁻¹ -1 ; The OH group content is 80wt.ppm–150wt.ppm; Maximum stress value ≤ 0.35 MPa; The maximum diameter that can be produced is 650 mm.
[0011] A further technical solution is that the chemical vapor deposition method includes using high-purity silicon tetrachloride as the silicon source material. The purity of the silicon tetrachloride is ≥99.9999%, and the mass fraction of Li, Na, K, Mg, Ca, Ti, Cr, Fe, Ni, and Cu metal impurities is ≤10 μg / kg, and the total mass concentration of chlorine-containing organic impurities is ≤50 μg / kg. The detection method is based on GB / T14849.1-2015. The silicon tetrachloride raw material is purified by distillation before use. The distillation temperature is 57℃±0.5℃, the reflux ratio is 10:1, and the middle fraction, which accounts for 60%–80% of the total feed, is collected as the raw material for deposition.
[0012] A further technical solution is that the chemical vapor deposition method also includes a sintering process: the deposited porous preform is heated to 1200℃ at a rate of 1℃ / min and held for 2 hours under vacuum or an inert atmosphere; then, it is heated to 1450℃-1500℃ at a rate of 0.5℃ / min and held for 4-6 hours for vacuum sintering, with a furnace pressure ≤1×10⁻⁶. -2 Pa; when the temperature is raised to 1000℃, a mixture of helium gas containing 1vol%-5vol% deuterium is introduced for 2h-4h to adjust the OH group content to 80wt.ppm-150wt.ppm.
[0013] A further technical solution is that the chemical vapor deposition method also includes an annealing process: under an air atmosphere, the temperature is heated to 1050℃-1100℃ at 0.5℃ / min and held for 12h-24h for annealing, and then slowly cooled to 600℃ at 0.3℃ / min and then naturally cooled.
[0014] The present invention also provides a chemical vapor deposition apparatus for preparing the highly uniform synthetic quartz ingot, comprising a vertical cylindrical furnace body, the furnace body adopting a double-layer water-cooled structure, the inner wall material being high-purity quartz, and the apparatus further comprising: A detachable crucible structure, located within the furnace cavity, comprises a disc-shaped crucible bottom and a cylindrical crucible wall. The cylindrical crucible wall is cylindrical, with its lower end fixedly connected to an annular rotating platform. The annular rotating platform is connected to a second rotating drive mechanism for independent rotation of the cylindrical crucible wall. The disc-shaped crucible bottom is disc-shaped, with its center connected to a first rotating lifting mechanism via a downwardly extending connecting rod for independent rotation and lifting. The outer diameter of the disc-shaped crucible bottom is smaller than the inner diameter of the cylindrical crucible wall, and the disc-shaped crucible bottom is always located axially in the lower inner region of the cylindrical crucible wall, maintaining an annular gap between them. An annular guide plate is disposed between the air inlet and the exhaust outlet on the side wall of the furnace body. The annular guide plate has a vertical section and a horizontal section. The outer wall of the vertical section forms an annular guide channel with the inner wall of the furnace body. The horizontal section extends obliquely from the upper end of the vertical section towards the center of the furnace cavity, and is used to guide the hot air from the air inlet to be sprayed obliquely towards the center of the furnace cavity to form an annular rising air curtain.
[0015] A further technical solution is that the annular rotating platform is connected to the second rotating drive mechanism through an annular gear transmission structure on the lower outer periphery; a ring of exhaust ports is provided on the side wall of the furnace body 400mm from the bottom, and a ring of air inlets is provided 200mm below the exhaust ports; the vertical section has a height of 180mm, with its lower end lower than the upper edge of the air inlet and its upper end higher than the upper edge of the air inlet but lower than the lower edge of the exhaust port, so that the vertical section completely covers the furnace wall between the upper edge of the air inlet and the lower edge of the exhaust port; the outlet end of the horizontal section is lower than the lower edge of the exhaust port, with an inclination angle α=45°.
[0016] A further technical solution is that the inner wall of the furnace is integrally formed with a streamlined cross-section annular support platform at a corresponding height, and the upper end of the vertical section is provided with an outward flange, which is placed and fixed on the upper surface of the annular support platform; the radial protrusion width of the annular support platform is 15mm-25mm, and its windward and leeward sides are both arc-transitioned guide slopes.
[0017] A further technical solution is that the height of the annular support platform is 10mm-20mm, its lower end face is higher than the upper edge of the air inlet, and its upper end face is lower than the lower edge of the exhaust port; within the height range of the annular support platform, the radial width of the flow guide channel is 15mm-25mm; in the areas above and below the annular support platform, the radial width of the flow guide channel is maintained at 30mm-50mm.
[0018] A further technical solution is that 16-32 vent holes are evenly opened along the circumference of the outward flange, and the total flow area of the vent holes is not less than 80% of the cross-sectional area of the guide channel; or, the outward flange is a segmented structure, consisting of multiple independent flange lugs arranged at intervals along the circumference, with the gap between adjacent lugs serving as an airflow channel.
[0019] A further technical solution is that the diameter of the bottom of the disc-shaped crucible is 600mm and the thickness is 30mm; the inner diameter of the cylindrical crucible wall is 610mm and the height is 300mm; the width of the annular gap is 5mm-10mm; the connecting rod passes through the central opening of the annular rotating platform, and a dynamic sealing bearing is provided between the two.
[0020] The advantages and beneficial effects of this invention are as follows: Significantly improved refractive index uniformity: By using an independently temperature-controlled dish bottom and an annular gas curtain isolation technology, the temperature gradient of the deposition target surface is controlled within 5℃. Combined with real-time feedback adjustment, the refractive index uniformity of the quartz ingot reaches δn≤1×10⁻⁶. -6 It is superior to existing technologies (δn≈2×10). -6 ).
[0021] Improved stability of the deposition process: The rising air curtain formed by the annular guide plate effectively isolates the deposition reaction zone from the furnace wall, solving the problems of airflow recirculation and dust pollution caused by the obstruction of the cylinder wall in the existing crucible deposition. At the same time, the gradually decreasing pressure distribution ensures the smooth discharge of dust and exhaust gas.
[0022] Large-size preparation capability: In the split crucible structure, the disc-shaped crucible bottom can be raised and lowered independently, breaking through the limitation of cylindrical crucibles on deposition height. Combined with the multi-blowtorch layout, it is possible to prepare large-size quartz ingots with a diameter ≥600mm and a height ≥200mm.
[0023] Excellent resistance to laser damage: The OH group content is controlled at 50-200 wt.ppm and is evenly distributed. Combined with hydrogen molecule doping, the absorption coefficient changes very little under ArF excimer laser irradiation, which meets the requirements for long-term stable operation of lithography machines. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of a chemical vapor deposition apparatus for a high-uniformity synthetic quartz ingot used in a semiconductor lithography lens according to the present invention. Figure 2 This is a schematic diagram of the comparative example in Embodiment 2 of the present invention; Figure 3 This is a schematic diagram of Embodiment 4 of the present invention; Figure 4 yes Figure 3 A partially enlarged schematic diagram of the central ring support platform and its surrounding area.
[0025] In the diagram: 1. Furnace body; 2. Flange; 3. Vent hole; 4. Ridge; 6. Exhaust port; 8. Inlet; 11. Annular guide plate; 12. Annular support platform; 41. Disk-shaped crucible bottom; 42. Cylindrical crucible wall; 43. Connecting rod; 44. Annular rotating platform; 45. Annular gap; 51. First rotating lifting mechanism; 52. Second rotating drive mechanism; 111. Vertical section; 112. Horizontal section. Detailed Implementation
[0026] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.
[0027] Example 1: This invention relates to a highly uniform synthetic quartz ingot for semiconductor photolithography lenses, using high-purity silicon tetrachloride (SiCl4) as the silicon source. The SiCl4 purity is ≥99.9999% (mass fraction), with the total mass concentration of Li, Na, K, Mg, Ca, Ti, Cr, Fe, Ni, and Cu metallic impurities ≤10 μg / kg (ppb w / w), and the total mass concentration of chlorinated organic impurities ≤50 μg / kg (ppb w / w). The detection method follows GB / T 14849.1-2015. Before use, the raw material is purified by distillation at 57℃±0.5℃ with a reflux ratio of 10:1. The middle fraction, accounting for 60%–80% of the total feed, is collected as the deposition material.
[0028] The core structure of the chemical vapor deposition apparatus used in this embodiment is as follows: Figure 1 As shown, the specific configuration is as follows: (1) Structure of furnace body and crucible The chemical vapor deposition apparatus includes a vertical cylindrical furnace body 1, employing a double-layer water-cooled structure. The inner wall is made of high-purity quartz, with a diameter of 1500 mm and a height of 2500 mm. The furnace chamber contains a separable crucible structure, consisting of a disc-shaped crucible bottom 41 and a cylindrical crucible wall 42. The cylindrical crucible wall 42 is a cylinder with an inner diameter of 610 mm and a height of 300 mm, its lower end fixedly connected to an annular rotating platform 44. The annular rotating platform 44 is connected to a second rotary drive mechanism 52 via an annular gear transmission structure on its lower outer periphery, enabling independent rotation of the cylindrical crucible wall (fixed height, no lifting or lowering). The disc-shaped crucible bottom 41 is a disc with a diameter of 600 mm and a thickness of 30 mm, its center connected to a first rotary lifting mechanism 51 via a downward-extending connecting rod 43, enabling independent rotation and lifting. The outer diameter of the disc-shaped crucible bottom 41 is smaller than the inner diameter of the cylindrical crucible wall 42, ensuring that the disc-shaped crucible bottom 41 is always located axially in the lower inner region of the cylindrical crucible wall 42, with a 5mm-10mm annular gap 45 between them. This gap is used to balance the gas pressure inside the furnace cavity and reduce the overflow of deposited dust. The connecting rod 43 passes through the central opening of the annular rotating platform 44, and a dynamic sealing bearing is provided between them to prevent gas and dust inside the furnace cavity from leaking into the external environment.
[0029] (2) Annular guide vane and fixing structure A ring of exhaust ports 6 is located 400mm from the bottom on the side wall of furnace body 1, and a ring of air inlets 8 is located 200mm below the exhaust ports, i.e., 350mm from the bottom. An annular guide plate 11 is positioned between the air inlets 8 and the exhaust ports 6. An annular support platform 12 with a streamlined cross-section is integrally formed on the inner wall of furnace body 1 at a corresponding height. Its radial protrusion width is 15mm-25mm, and both the windward and leeward sides are curved guide surfaces with rounded transitions. An outward-facing flange is provided at the upper end of the vertical section 111 of the annular guide plate 11, which rests and is fixed to the upper surface of the annular support platform 12. 16-32 vent holes are evenly distributed circumferentially on the outward-facing flange. The total flow area of the vent holes is not less than 80% of the cross-sectional area of the guide channel. The cross-sectional area of the guide channel is calculated based on the annular area between the inner diameter of the furnace body and the outer wall of the vertical section of the guide plate. The total area of the vent holes is determined by multiplying the area of a single hole by the number of holes, allowing the rising airflow to pass through the flange and enter the horizontal section guidance area. The vertical section 111 of the annular guide plate 11 is a cylindrical annular plate coaxially arranged with the furnace body, forming an annular guide channel between its outer wall and the inner wall of the furnace body; the horizontal section 112 is a conical annular plate extending obliquely from the upper end of the vertical section towards the center of the furnace cavity, with its radial diameter at the gas outlet end being smaller than that of the vertical section, forming a conical structure that converges towards the center of the furnace cavity. Due to the conical structure of the horizontal section, the airflow cross-section gradually decreases and the flow velocity gradually increases under the guidance of the horizontal section, eventually being ejected from the gas outlet end at a 45° oblique direction, forming a high-speed annular gas curtain around the deposition reaction zone.
[0030] As an alternative, the outward-facing flange can adopt a segmented structure, consisting of multiple independent flange lugs arranged at intervals along the circumference, with the gaps between adjacent lugs serving as airflow channels.
[0031] Key dimensions and positional relationships: The vertical section 111 of the annular guide plate 11 has a height of 180mm. Its lower end, at 370mm, is lower than the upper edge of the air inlet 8 (360mm), and its upper end, at 550mm, is higher than the air inlet 8 but lower than the lower edge of the exhaust port 6 (600mm), completely covering the furnace wall between the upper edge of the air inlet and the lower edge of the exhaust port. The annular support platform 12 has a height of 10mm-20mm and is installed on the inner wall of the furnace body 1, located at the fixed connection between the upper end of the vertical section 111 and the annular guide plate 11. The lower end of the annular support platform 12 is higher than the upper edge of the air inlet 8, and the upper end is lower than the lower edge of the exhaust port 6. That is, the annular support platform 12 only covers a portion of the furnace wall between the air inlet 8 and the exhaust port 6 in the height direction. An annular guide channel is formed between the outer wall of the vertical section 111 and the inner wall of the furnace body 1. Within the height range of the annular support platform 12, the flow guide channel is formed by the outer wall of the vertical section 111 and the inner edge of the annular support platform 12, with a radial width of 15mm-25mm to increase the flow velocity. Compared with the support platform area, the width of the flow guide channel in the non-support platform area is increased to reduce flow resistance. In the areas above and below the annular support platform 12, the radial width of the flow guide channel is maintained at 30mm-50mm. This 30mm-50mm non-narrowing area width serves as the reference flow cross-section of the flow guide channel, and the width narrowing ratio of the support platform area is referenced to this. The horizontal section 112 of the annular guide plate 11 extends inclinedly from the upper end of the vertical section, i.e., at a height of 550mm, towards the center of the furnace cavity. The height of the gas outlet end is 580mm, which is 600mm lower than the lower edge of the exhaust port 6, with an inclination angle α=45°.
[0032] (3) Airflow path and function Air supply path: Hot air supplied from the bottom enters through inlet 8. The hot air temperature is 200℃-400℃, and the flow rate is 300L / min-600L / min. The hot air first enters the guide channel between the vertical section 111 and the furnace wall and flows upward. The channel width narrows when flowing through the annular support platform 12, and then passes through the vent hole of the flange at the upper end of the vertical section 111. Under the forced guidance of the horizontal section 112, it is sprayed obliquely towards the center of the furnace cavity. The streamlined design of the annular support platform 12 ensures that the equivalent flow area of the guide channel is not significantly reduced.
[0033] Airflow function and direction: The obliquely ejected hot airflow forms an annular rising air curtain radially around the deposition reaction zone, 20mm-200mm above the crucible. This air curtain acts as a thermal insulator, separating the reaction zone from the cold furnace wall, preventing cold wall radiation from affecting the temperature uniformity of the target surface, and preventing dust contamination of the furnace wall. After completing its thermal insulator function, the annular rising air curtain merges with the reaction waste gas HCl and dust in the area 180mm-200mm above the crucible, i.e., outside the deposition reaction zone, and continues to rise along the central area of the furnace cavity, finally exiting through exhaust port 6.
[0034] Pressure distribution: The relative negative pressure at the exhaust port is maintained between -100Pa and -150Pa, which is linked with the gas supply pressure to form a pressure distribution in the furnace cavity that gradually decreases from the target surface to the exhaust port: exhaust port P1 < guide plate P2 < target surface P3, ensuring unidirectional and orderly airflow without short circuits or backflow.
[0035] After distillation, the SiCl4 is vaporized and introduced into 18 oxyhydrogen flame torches at the top of the furnace at a flow rate of 1000-2000 sccm. The torches are arranged in concentric circles: 4 in the inner ring, 6 in the middle ring, and 8 in the outer ring. Simultaneously, high-purity hydrogen gas at a flow rate of 50-150 L / min and high-purity oxygen gas at a flow rate of 25-75 L / min are introduced. The SiCl4 hydrolyzes in the oxyhydrogen flame to form SiO2 particles, which are deposited on the upper surface of the bottom of the dish-shaped crucible 41.
[0036] Deposition parameters: furnace temperature 1200℃-1400℃, initial temperature of the bottom of the disc crucible 400℃-600℃, rotation speed 5rpm-20rpm, lifting speed 0.5mm / h-5mm / h.
[0037] Closed-loop control of target surface temperature field: A K-type thermocouple array with 24 temperature measuring points is embedded on the upper surface of the bottom 41 of the disc-shaped crucible to monitor the target surface temperature in real time. The 24 temperature measuring points are arranged in 3 rings × 8.
[0038] The controller performs intelligent adjustments based on feedback: Adjusting the lifting speed: When the center temperature of the target surface is more than 5°C higher than the edge temperature, increase the lifting speed to move the target surface away from the burner to reduce the center temperature; when the center temperature of the target surface is more than 5°C lower than the edge temperature, reduce the lifting speed or appropriately reduce the distance between the target surface and the burner to increase the center temperature.
[0039] Zoned air supply adjustment: Fine-tune the local temperature by adjusting the air supply flow rate at the corresponding zone's air inlet.
[0040] Independent control of multiple torches: In the initial stage of deposition (0-50mm), the inner and middle ring torches are turned on; in the middle stage (50-150mm), all torches are turned on; and in the later stage (above 150mm), the outer ring torches are gradually turned off to match the changes in deposition diameter and ensure uniformity of the temperature field.
[0041] Deposition continues until the porous dust preform reaches a diameter of 650 mm and a height of 250 mm.
[0042] The porous preform, along with the bottom of the disc-shaped crucible, is transferred to the sintering furnace. Under vacuum or inert atmosphere, the temperature is increased to 1200℃ at 1℃ / min and held for 2 hours; then increased to 1450℃-1500℃ at 0.5℃ / min and held for 4-6 hours for vacuum sintering (vacuum is achieved by pumping to the target pressure using a molecular pump group, and monitored in real-time with a high-precision vacuum gauge; furnace pressure ≤ 1×10⁻⁶). −2 The vacuum level (Pa) is maintained throughout the entire sintering and heat preservation stage. When the temperature is raised to 1000℃, a helium mixture containing 1 vol%-5 vol% deuterium (D2) is introduced for 2-4 hours to adjust the OH group content to 80wt.ppm-150wt.ppm.
[0043] After sintering, the temperature is cooled to 800℃ at a rate of 0.5℃ / min, and then allowed to cool naturally. Finally, the temperature is heated to 1050℃-1100℃ at a rate of 0.5℃ / min in air for annealing for 12-24 hours, and then slowly cooled to 600℃ at a rate of 0.3℃ / min before being allowed to cool naturally to relieve stress.
[0044] The synthetic quartz ingots prepared by the above method have the following performance indicators:
[0045] Compared with comparative examples (CN117776505A, CN118993508A, etc.), the core indicators of the synthetic quartz ingot of the present invention are significantly better than those of the prior art.
[0046] Alternative to Implementation Example 1 In another alternative implementation, the silicon source material can be an organosilane such as octamethylcyclotetrasiloxane instead of silicon tetrachloride, with a vaporization temperature of 120℃-180℃, high-purity nitrogen as the carrier gas, oxygen or nitrous oxide as the oxidizing gas, and a deposition temperature controlled at 1000℃-1200℃. This method uses chlorine-free raw materials, eliminating the need for chlorine impurity removal processes, and the OH group content of the product can be as low as 10wt.ppm-50wt.ppm.
[0047] Example 2: Unlike Example 1, in existing vertical CVD processes, absolute laminar flow stability of the airflow is generally pursued to ensure deposition uniformity. However, as described in the background section (see the paper by Zhou Jianxin et al.), even with macroscopically stable airflow, the deposited quartz ingot still exhibits a periodic layered structure with a thickness of approximately 0.16 cm perpendicular to the growth direction. This example study found that the formation of the layered structure is not due to macroscopic airflow instability, but rather to a fixed spatial phase coupling between the excessively stable laminar flow field and the uniform rotation of the target surface. This causes the deposition particles to overlap periodically in the radial position per unit time, leading to density fluctuations.
[0048] To address the aforementioned issues, this embodiment deliberately utilizes the slight airflow inhomogeneity caused by the machining tolerance of the vent holes on the annular guide plate flange, which is the defect in the traditional understanding, to amplify it into a controllable periodic pulsating airflow. This pulsation is then used to cancel out the dynamic averaging effect of the rotating target surface, thereby eliminating the layered structure at its source.
[0049] Based on the chemical vapor deposition apparatus described in Example 1, the upper vertical flange 2 of the annular guide plate 11 is modified asymmetrically as follows: the 24 vent holes 3 uniformly opened along the circumference of the flange (originally designed with equal diameter) are changed in this embodiment to have a sinusoidal diameter variation—that is, the diameter fluctuates periodically between 8 mm and 14 mm, and the diameter variation gradient between adjacent holes is ≤1 mm. Specifically, the diameter of the hole at the circumferential position θ is d(θ) = 11 + 3 × sin(4θ), forming a four-cycle alternating distribution of "large-small-large". Here, θ is in radians, and d is in mm; θ is the polar angle with the geometric center of the flange as the origin, and the zero point is taken as the circumferential starting position of any vent hole.
[0050] Local throttling structure of the guide plate support platform: On the windward side of the annular support platform 12, three trapezoidal cross-section micro-turbulence ridges 4 are set at 120° intervals along the circumference. The height of the ridges is 25mm, which is about 1 / 5 of the radial width of the annular support platform, and the width is 20mm. They are used to induce fixed vortices in the rising airflow to detach and then propagate along the circumference.
[0051] In traditional processes, the aforementioned asymmetrical structure is considered to disrupt airflow uniformity and is a design flaw that should be avoided at all costs. However, this embodiment takes the opposite approach, utilizing the sinusoidal variation of the orifice to create significant periodic pulsations in the circumferential flow rate of hot air entering the horizontal section 112 through the flange.
[0052] The circumferential pulsating hot airflow creates an asymmetric instantaneous temperature disturbance on the radial periphery of the upper surface of the target-faced disk bottom 41, causing periodic fluctuations in the local temperature of the deposition area around the target surface, with the fluctuation amplitude controllable within ±5℃.
[0053] Meanwhile, the bottom of the disc-shaped crucible rotates at 15 rpm. The key synergistic effect is that the rotation period of any point on the target surface is 4 seconds, which is greater than the airflow pulsation period, and the two are not integer multiples of each other, thus avoiding the formation of new fixed phase coupling.
[0054] Therefore, any micro-region on the target surface will experience 2-3 temperature / concentration fluctuations of different phases during one rotation. These fluctuations are completely averaged over time, resulting in the deposition rate remaining constant over all radii of the target surface over time.
[0055] The final result is that the spatial periodic density fluctuations, i.e., the layered structure, caused by the fixed laminar flow and uniform rotation are completely smoothed out. Testing revealed that no obvious layered striations were observed on the cross-section of the precast body after deposition, the periodic stress distribution characteristics were significantly reduced, and the maximum stress value was reduced by more than 50% compared to existing technologies, preferably to below 0.2 MPa.
[0056] It should be noted that the amplitude of the above-mentioned airflow pulsation and temperature fluctuation can be adjusted within a certain range according to the furnace size, gas flow rate and target rotation speed. As long as the pulsation frequency and rotation frequency are not integer multiples, the effect of eliminating the layered structure can be achieved.
[0057] During the deposition stage, the bottom gas supply flow rate was set to 450 L / min, the hot air temperature to 300℃, the target rotation speed to 15 rpm, and the lifting speed to 2 mm / h. At this lifting speed, the formation of the layered structure was mainly related to the single-circle rotating deposition path, rather than the longitudinal growth thickness.
[0058] The range of change in the vent diameter can be adjusted in conjunction with the rotation speed of the target surface. To ensure that the pulsation frequency and the rotation frequency remain non-integer multiples at different rotation speeds, the vent diameter fluctuation range is set at a ratio of 0.5 × (rotation speed / 10) mm. This ensures that the pulsation frequency and the rotation frequency remain non-integer multiples at different rotation speeds, thus guaranteeing that the pulsation frequency and the rotation frequency always remain non-integer multiples.
[0059] The remaining deposition parameters remained the same as in Example 1, such as furnace temperature of 1300℃, initial target temperature of 500℃, and SiCl4 flow rate of 1500 sccm.
[0060] To verify the decisive influence of the annular guide vane's installation direction on the air curtain effect, comparative example 3 was set up: the annular guide vane was installed upside down, so that the horizontal section was located at the lower part of the furnace body, i.e., at a height of 400mm, and was hung on the annular support platform via a flange, while the vertical section extended from the horizontal section to a height of 580mm from the upper part of the furnace body. Figure 2As shown (since the flange is hung on the annular support platform, no distinction is made for ease of illustration; the actual thickness is thicker than shown, and is the combined thickness of the flange and the annular support platform). All other process parameters are exactly the same as in Example 2.
[0061] Experimental results: The effective utilization rate of the supplementary air in Comparative Example 3 was only about 38%, and a large amount of hot air was drawn away by the exhaust port without being properly guided after entering through the air inlet; the target surface temperature gradient reached more than 15℃, and the refractive index uniformity of the prepared quartz ingot was δn=1.8×10 -6 Experiments have shown that the vertical section at the bottom and the horizontal section at the top is the structural basis for the effective isolation of the reaction zone by the air curtain. Reversing the vertical direction of the guide plate will lead to failure of thermal isolation, short circuit of air supply, retention of exhaust gas, and a sharp deterioration in product uniformity.
[0062] Example 3: Unlike Example 1, this example improves the annealing process based on the deposition apparatus and process of Example 1. It is also applicable to the organosilane feedstock route in the alternative scheme of Example 1. After densification sintering, the diameter of the porous preform shrinks to approximately 520mm-580mm, and the height shrinks to approximately 180mm-210mm. In the apparatus described in Example 1, the annular rising gas curtain generated by the annular guide plate is used for thermal isolation during the deposition stage. When the diameter of the quartz preform reaches 650mm and the height reaches 250mm, densification sintering forms a quartz ingot with a diameter of 520mm-580mm and a height of 180mm-210mm. Traditional processes require transferring this quartz ingot to a separate sintering furnace for sequential densification sintering and annealing (see steps in Example 1). However, the transfer process is highly susceptible to introducing contamination and thermal shock cracks. Even when annealed in a sintering furnace, large quartz ingots with diameters of 520mm-580mm have a significant difference in heat dissipation rates between the center and the edge. The edge has a small heat capacity and dissipates heat quickly, which often leads to a radial temperature difference of more than 50°C, ultimately resulting in residual stress that cannot be eliminated.
[0063] This embodiment utilizes the fact that the deposition furnace and the annealing furnace share the same furnace cavity. The gas curtain used for heat insulation in the deposition stage is switched to an active auxiliary heat dissipation tool in the annealing stage. This achieves functional complementarity of the same set of flow guiding structures in different processes, avoids the transfer of contaminants, and improves the uniformity of annealing.
[0064] Specifically, the deposition furnace used in this embodiment is equipped with a heating system with a maximum operating temperature of not less than 1600°C, such as graphite resistance heating or induction heating. During the deposition stage, only the oxyhydrogen flame is used as the heat source, while the furnace body heating system is used during the sintering and annealing stages, thus achieving multiple uses for one furnace.
[0065] No physical modifications are required to the original furnace structure; only two auxiliary components are added: a gas path switching and temperature control system and an edge temperature monitoring unit.
[0066] The gas path switching and temperature control system includes a dual-channel gas mixing valve added upstream of the bottom air inlet. One channel is connected to a high-temperature air heater with a temperature of 200℃-450℃, and the other channel is connected to a low-temperature nitrogen cooler with a temperature of room temperature to 100℃. The two channels can be mixed proportionally according to the program control to output any set temperature within the range of 20℃-450℃.
[0067] The edge temperature monitoring unit includes three infrared temperature measurement channels evenly spaced circumferentially on the side wall of the furnace body, corresponding to the middle section of the outer wall of the quartz ingot, that is, 150mm-200mm below the horizontal section of the guide plate in the height direction, approximately 380mm-430mm from the bottom. Infrared-transmitting optical windows, such as zinc sulfide windows, are installed within the temperature measurement channels. Three infrared pyrometers are respectively installed at the corresponding positions of the windows on the outer side of the furnace wall. Each infrared pyrometer's temperature measurement channel is equipped with an inert gas purging structure at its front end. This structure consists of a stainless steel purging tube, 50mm-80mm in length and 30mm-40mm in inner diameter, sealed at one end to the furnace wall window via a flange, and the infrared pyrometer mounted at the other end. A 6mm diameter inlet is located in the middle of the purging tube, through which high-purity nitrogen (≥99.999% purity, flow rate 1L / min-3L / min, standard conditions) is introduced. The nitrogen flows along the inner wall of the purging tube towards the furnace wall, forming a positive pressure curtain in front of the window glass. This prevents dust and hot gas from accumulating or condensing on the window surface, ensuring a clear light path for temperature measurement. Through this window and the purging tube, the infrared pyrometer precisely targets the annular area in the middle section of the outer wall of the quartz ingot (approximately 380mm-430mm from the bottom), monitoring its temperature in real time. Based on the pyrometer's field of view (FOV, the angular range from which the instrument can receive infrared radiation), the size of the target area it can cover can be calculated. To ensure measurement accuracy, the aiming point of the pyrometer needs to be calibrated using mechanical tooling before the formal measurement. The center temperature is obtained in real time by using a single-point infrared pyrometer positioned vertically downwards on the furnace top and aligned with the center area of the upper surface of the quartz ingot; the edge temperature is characterized by the average value of the three circumferential infrared pyrometers mentioned above.
[0068] During the deposition stage, the high temperature of the 300°C gas curtain is used to isolate the cold furnace wall from radiation, which is its positive function. However, when transitioning to the annealing stage, the gas curtain itself becomes an additional heat source for the edge area, which is conventionally believed to exacerbate edge overheating and constitute a thermal defect.
[0069] This embodiment reverses the use of this defect. After the annealing and constant temperature holding is completed, the gas temperature at the inlet is actively reduced from 300℃ in a preset step, and the flow rate is maintained at the standard state of 500L / min. The flow rate is automatically adjusted according to the furnace pressure, and the apparent gas velocity is controlled within the range of 2m / s-8m / s.
[0070] The low-temperature air curtain is sprayed obliquely along the original path towards the annular area 20mm-50mm around the quartz ingot, providing controllable forced convection cooling to the edge.
[0071] By adjusting the temperature and flow rate of the low-temperature air curtain, the cooling rate of the quartz ingot's edge is forcibly reduced to match the natural radiation cooling rate of the central area; both are measured to be controlled at 0.5℃ / min. Specifically, when the infrared pyrometer shows that the edge temperature is more than 10℃ lower than the center temperature, the air curtain temperature is automatically increased or the flow rate is decreased; conversely, the air curtain temperature is decreased or the flow rate is increased.
[0072] Therefore, during the entire annealing and cooling process, the cooling process of each point on the radial section of a large-sized quartz ingot is almost the same, and thermal stress will not be generated due to differences in thermal history.
[0073] The final result is that after annealing, the maximum residual stress in the quartz ingot is reduced from ≥0.8MPa in the traditional process to ≤0.3MPa, and there is no need to transfer large-sized quartz ingots from the deposition furnace to a separate sintering furnace, eliminating the risk of transfer damage and contamination.
[0074] After deposition is complete, immediately start the sintering-annealing process after turning off the oxyhydrogen flame torch; no cooling is required before unloading.
[0075] Under vacuum or inert atmosphere, the furnace pressure is ≤1×10⁻⁶. -2 The furnace temperature was increased from approximately 1300℃ (the end temperature of deposition) to 1450℃ at a rate of 1℃ / min, and held at this temperature for 4 hours for vacuum sintering to achieve complete densification of the porous preform. During the vacuum sintering stage, the gas curtain was not used, and the bottom air inlet was closed.
[0076] After densification, an inert protective gas, such as nitrogen or argon, is introduced into the furnace cavity to stabilize the furnace pressure within the range of 100Pa-1000Pa. Then, the cooling phase begins, with the temperature decreasing from 1450℃ to 800℃ at a rate of 0.5℃ / min throughout the process. Simultaneously, a gas curtain temperature control program is executed. At temperatures above 1200℃, the air curtain temperature is 300℃, which is lower than the furnace temperature but still higher than the water-cooled furnace wall temperature. The water-cooled furnace wall temperature is about 50℃-80℃, which can form a buffer layer between the air curtain and the furnace wall, reducing the cold radiation effect of the furnace wall on the quartz ingot.
[0077] Within the 1200℃→800℃ range, the air curtain temperature is adjusted in real time according to a linear relationship of T_air curtain = 0.25 × T_ingot + 50, where T_ingot is the measured value from an infrared pyrometer. Through thermodynamic simulation and experimental calibration, when the air curtain temperature satisfies the relationship T_air curtain = 0.25 × T_ingot + 50, the convective heat transfer at the edge of the quartz ingot is basically matched with the radiative heat transfer at the center, achieving synchronous cooling rates between the edge and center. Here, T_ingot is the measured edge temperature of the quartz ingot using an infrared pyrometer, and T_air curtain is the temperature of the air curtain gas.
[0078] Below 800℃, the gas curtain heater is turned off, and only room temperature nitrogen is introduced at a flow rate of 500L / min. At this time, the heat capacity of the quartz ingot has been significantly reduced, and the temperature difference between the center and the edge naturally converges to within 5℃. No active temperature control is required, and it is allowed to cool naturally to room temperature.
[0079] The entire annealing process is completed in situ within the deposition furnace, eliminating the need for relocation and saving the use of a separate sintering furnace.
[0080] Example 4: The difference from Example 1 is that, as shown in Example 4... Figure 3 , Figure 4 As shown, this embodiment redesigns the structure of the annular support platform 12, with the following specific differences: In Embodiment 1, the annular support platform adopts a streamlined cross-section, a radial protrusion of 15mm–25mm, and a guide channel width of 15mm–25mm; while in this embodiment, the annular support platform is constructed as an annular throttling structure with a sharp edge, a radial protrusion width of 25mm–35mm, preferably 30mm, and the radial width of the guide channel within the support platform interval is narrowed to 8mm–12mm, preferably 10mm. The axial height of the support platform, i.e., the length of the throttling interval, is 15mm–20mm. In common knowledge in the art, the radial protrusion of the annular support platform 12 narrows the guide channel, leading to increased airflow resistance, increased local pressure drop, and induced turbulent disturbances. Therefore, traditional designs generally adopt streamlined or arc-shaped transition cross-sections to minimize the blocking effect and maintain a smooth upward flow of air. However, the inventors of this application unexpectedly discovered that the throttling effect, which was considered a defect, could be used under certain conditions to solve another, more intractable defect: the segmented jet problem caused by circumferential machining deviations in the flange vent holes. The circumferential machining deviations in the flange vent holes are generally ±10%–±15%. The inconsistent effective flow areas of each hole cause the airflow to be ejected in a discrete sector pattern after entering the horizontal section 112, forming weak airflow areas, or cold spots, between adjacent sectors, making it impossible to form a continuous and uniform annular air curtain.
[0081] Based on this, this embodiment adopts reverse thinking. Instead of eliminating the throttling and narrowing of the support platform, it actively strengthens it by constructing the annular support platform as an annular throttling structure with sharp edges, so that the airflow is accelerated in the narrowing range to a critical flow velocity sufficient to induce strong turbulent mixing. The radial momentum exchange effect is used to forcibly smooth out the circumferential flow deviation in a short distance.
[0082] The specific structural parameters are as follows: The cross-section of the annular support platform is rectangular or trapezoidal, with no rounded chamfers on the windward and leeward sides, or a chamfer radius R ≤ 0.5mm, forming a sharp-edge throttling boundary; 16–32 vent holes are evenly opened circumferentially on the outward-facing flange, with the total flow area of the vent holes being 60%–80% of the cross-sectional area of the guide channel, appropriately reduced compared to the proportion in Example 1, to further enhance the airflow penetration speed in conjunction with the throttling effect; the processing deviation of the vent holes is controlled within ±10%–±15%, which is considered a defect in conventional design, but is precisely the applicable scenario for the throttling and rectification effect in this scheme. Except for the structural change of the annular support platform, the geometric dimensions and spatial positions of the vertical and horizontal sections of the annular guide plate are consistent with those in Example 1, with the horizontal section outlet height still being 580mm and the tilt angle α = 45°. It should be noted that the above-mentioned numerical range is traditionally considered a design range that should be avoided. However, if the channel width is greater than 15mm, the flow velocity will be below the critical threshold of 8m / s, which is insufficient to activate momentum exchange; if it is less than 5mm, the pressure drop will be too large and it will easily cause blockage. Therefore, 8mm–12mm is the preferred range that balances rectification effect and pressure drop control. Alternatively, the inner wall of the annular rotating stage 44 can be provided with teeth, and the rotation of the annular rotating stage 44 can be achieved through gears meshing with the teeth, and then through a second rotating drive mechanism 52 connected to the gears.
[0083] According to the fluid continuity equation Q=v·A, when hot air enters the guide channel at a flow rate of 300L / min–600L / min, the flow velocity in the non-narrowing region is about 1–2m / s; after reaching the support platform area, the channel width drops sharply to 8mm–12mm, the flow cross-sectional area is reduced to less than 1 / 5, and the flow velocity rises sharply to 8–12m / s. The following physical effects are produced at high flow rates: (1) Radial momentum exchange, the velocity gradient of the cross section induces shear stress, which promotes radial migration and mixing of airflow micro-particles; (2) Circumferential uniform flow, the turbulent diffusion coefficient is increased by 1-2 orders of magnitude compared with the laminar state, even if there is a ±15% flow deviation in the vent, the circumferential non-uniformity can be compressed to within ±3% after passing through the 15mm-20mm throttling interval, and the rectification effect is best when it is 20mm; (3) Jet rigidity is improved, entering the horizontal section at 8-12m / s, which is 3-4 times higher than the 2-3m / s in the non-throttling state, and the anti-disturbance ability is enhanced; (4) Pressure distribution reconstruction, the static pressure upstream of the throttling rises to 150Pa-250Pa, ensuring that the air supply pressure of each vent is consistent, and reducing the deviation between vents from the source.
[0084] Comparative experiments show that, under the same conditions, this embodiment, with a support platform channel width of 10mm and a throttling and rectifying type, compared with the comparative example (support platform channel width of 40mm, streamlined cross-section, no throttling structure), improves the flange outlet circumferential flow deviation from ±12% to ±2.8%, narrows the horizontal section outlet circumferential temperature difference from ±10℃ to ±3℃, and transforms the annular air curtain from having obvious segmented jets to continuous and complete. Based on the same 24-point thermocouple array as in Example 1, the radial temperature uniformity of the deposition target surface is optimized from ±18℃ to ±6℃. The trade-off is an increase in the pressure drop of the guide channel from 55Pa to 185Pa. This increase in pressure drop can be compensated by increasing the inlet flow rate from the basic operating condition of 300L / min–600L / min to 500L / min–800L / min. After compensation, the system pressure drop is still lower than the upper limit of the rated operating pressure of the gas supply system, and the operational stability is not affected.
[0085] Example 5: Unlike Example 1, the annular gap is not closed or reduced. Instead, the gap is actively used as a heat replenishment channel. A portion of the hot air from the air inlet is diverted and blown upward through the gap to locally heat the edge area of the upper surface of the crucible bottom, thus solving the problem of low edge temperature.
[0086] In common knowledge in this field, the annular gap is considered a necessary defect. Although it serves to balance the gas pressure, it causes heat radiation to dissipate downwards from the bottom edge of the crucible, resulting in a significantly lower edge temperature than the center. The traditional approach is to minimize the gap to less than 3 mm or to add a heat insulation ring.
[0087] This application takes the opposite approach, instead of narrowing the gap, it appropriately widens it to 8mm–15mm, and diverts a separate stream of hot air from the air inlet through this gap to blow upwards, forming an annular edge-heating air curtain. The heat loss channel is reversed into an edge-heating channel, eliminating the need for additional blowtorches or heating wires.
[0088] The width of the annular gap is set to 8mm–15mm, preferably 10mm–12mm, which is 2–3 times larger than the conventional value of 3mm–5mm. This provides sufficient flow cross-section for the heat-replenishing airflow, ensuring that the airflow rises steadily at 1m / s–3m / s to form a uniform heat-replenishing layer. It should be noted that although the increased gap will increase downward heat radiation loss, the temperature of the heat-replenishing airflow (500℃–700℃) is higher than the temperature at the bottom edge of the crucible (400℃–550℃). The direction of heat transfer is reversed from downward heat leakage to upward heat replenishment, fundamentally changing the function of the gap.
[0089] Regarding the distribution piping, a ring-shaped distribution pipe is pre-embedded at the bottom of the furnace body, connecting to the main air inlet. An independent mass flow controller and electric heater are installed on the pipe, with 8–16 air outlets evenly distributed circumferentially opposite the gap. An alternative solution is to utilize the dynamic seal gap as a distribution channel, eliminating the need for additional piping.
[0090] Regarding the supplementary heating parameters, the temperature is controlled at 500℃–700℃, preferably 600℃–650℃, and the flow rate is controlled at 50L / min–150L / min, preferably 80L / min–120L / min, which is about 10%–20% of the main flow rate, to heat the edges in a gentle convection manner and avoid thermal shock.
[0091] In the original design, with a gap width of 5mm and no additional heating, the temperature difference between the edge and the center was 45℃, resulting in an effective utilization rate of 78%. In the comparative example, when the gap was reduced to 3mm and no additional heating was provided, the temperature difference only decreased to 38℃, resulting in an effective utilization rate of 82%. However, in this embodiment, by expanding the gap to 12mm and combining it with additional heating at 600℃ and 100L / min, the temperature difference plummeted to 4℃, and the effective utilization rate increased to 93%. Simply reducing the gap provides limited improvement, while expanding the gap combined with additional heating significantly reduces the temperature difference. The traditionally avoided practice of expanding the gap has become crucial for improving uniformity.
[0092] This embodiment is linked with a 24-point K-type thermocouple array. When the average temperature at the edge is more than 5°C lower than that at the center, the heating is automatically increased to the upper limit of 150L / min and 700°C. When the temperature at the edge is more than 5°C higher than that at the center, the heating is automatically reduced or turned off to the lower limit of 30L / min and 450°C, thus achieving dynamic adaptive adjustment of radial temperature difference ≤ ±5°C throughout the entire deposition cycle.
[0093] Alternatively, the annular gap width can be adjusted within the range of 6mm–20mm, preferably 8mm–15mm. The reheating temperature can be adjusted within the range of 450℃–800℃, and the flow rate can be adjusted within the range of 30L / min–200L / min. An independent gas supply system can be set up to completely eliminate interference with the main pipeline, and the gas can be replaced with high-purity nitrogen or argon to avoid the introduction of hydroxyl groups.
[0094] The original design had a temperature difference of 45°C between the edge and center, and a refractive index uniformity of 1.5 × 10⁻⁶. -6 The edge utilization rate is 78%. This embodiment reduces the temperature difference to 4°C and improves the refractive index uniformity to ≤0.6×10⁻⁶. -6 The edge utilization rate is increased to 93%, and no additional heating equipment is required; the improvement is achieved simply by utilizing the gap diversion. In this embodiment, the heat loss gap is reversed into an edge heat replenishment channel. Expanding the gap, an operation that is generally avoided in the art, becomes the key to improving the heat replenishment efficiency in this solution, forming the core support for the inventive proof.
[0095] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A high-uniformity synthetic quartz ingot for use in semiconductor photolithography lenses, characterized in that, The synthetic quartz ingot is prepared by chemical vapor deposition and has the following performance characteristics: refractive index uniformity δn ≤ 0.9 × 10⁻⁶. -6 The test wavelength was 633nm, and the measurement was performed using an interferometer according to ISO 10110-14. Birefringence ≤2.5nm / cm, test wavelength 633nm; Initial absorption coefficient at 193 nm ≤ 0.0012 cm⁻¹ -1 ; The OH group content is 80wt.ppm–150wt.ppm; Maximum stress value ≤ 0.35 MPa; The maximum diameter that can be produced is 650 mm.
2. The high-uniformity synthetic quartz ingot for semiconductor photolithography lenses according to claim 1, characterized in that, The chemical vapor deposition method includes using high-purity silicon tetrachloride as the silicon source material. The purity of the silicon tetrachloride is ≥99.9999%, and the total mass concentration of metallic impurities (Li, Na, K, Mg, Ca, Ti, Cr, Fe, Ni, Cu) is ≤10 μg / kg, and the total mass concentration of chlorine-containing organic impurities is ≤50 μg / kg. The detection method is based on GB / T 14849.1-2015. Before use, the silicon tetrachloride raw material is purified by distillation at a temperature of 57℃±0.5℃ and a reflux ratio of 10:
1. The middle fraction, accounting for 60%–80% of the total feed, is collected as the raw material for deposition.
3. The high-uniformity synthetic quartz ingot for semiconductor photolithography lenses according to claim 2, characterized in that, The chemical vapor deposition method further includes a sintering process: the deposited porous preform is heated to 1200℃ at a rate of 1℃ / min and held for 2 hours under vacuum or inert atmosphere; then heated to 1450℃-1500℃ at a rate of 0.5℃ / min and held for 4-6 hours for vacuum sintering, with a furnace pressure ≤1×10⁻⁶. -2 Pa; when the temperature is raised to 1000℃, a mixture of helium gas containing 1vol%-5vol% deuterium is introduced for 2h-4h to adjust the OH group content to 80wt.ppm-150wt.ppm.
4. The high-uniformity synthetic quartz ingot for semiconductor photolithography lenses according to claim 3, characterized in that, The chemical vapor deposition method also includes an annealing process: under an air atmosphere, the temperature is heated to 1050℃-1100℃ at 0.5℃ / min and held for 12h-24h for annealing, and then slowly cooled to 600℃ at 0.3℃ / min and then allowed to cool naturally.
5. A chemical vapor deposition apparatus for preparing highly uniform synthetic quartz ingots as described in any one of claims 1 to 4, comprising a vertical cylindrical furnace body, said furnace body employing a double-layer water-cooled structure, the inner wall material being high-purity quartz, characterized in that, The device further includes: A detachable crucible structure, located within the furnace cavity, comprises a disc-shaped crucible bottom and a cylindrical crucible wall. The cylindrical crucible wall is cylindrical, with its lower end fixedly connected to an annular rotating platform. The annular rotating platform is connected to a second rotating drive mechanism for independent rotation of the cylindrical crucible wall. The disc-shaped crucible bottom is disc-shaped, with its center connected to a first rotating lifting mechanism via a downwardly extending connecting rod for independent rotation and lifting. The outer diameter of the disc-shaped crucible bottom is smaller than the inner diameter of the cylindrical crucible wall, and the disc-shaped crucible bottom is always located axially in the lower inner region of the cylindrical crucible wall, maintaining an annular gap between them. An annular guide plate is disposed between the air inlet and the exhaust outlet on the side wall of the furnace body. The annular guide plate has a vertical section and a horizontal section. The outer wall of the vertical section forms an annular guide channel with the inner wall of the furnace body. The horizontal section extends obliquely from the upper end of the vertical section towards the center of the furnace cavity, and is used to guide the hot air from the air inlet to be sprayed obliquely towards the center of the furnace cavity to form an annular rising air curtain.
6. The chemical vapor deposition apparatus according to claim 5, characterized in that, The annular rotating platform is connected to the second rotating drive mechanism via an annular gear transmission structure on its lower outer periphery; a ring of exhaust ports is provided on the side wall of the furnace body 400mm from the bottom, and a ring of air inlets is provided 200mm below the exhaust ports; the vertical section has a height of 180mm, with its lower end lower than the upper edge of the air inlet and its upper end higher than the upper edge of the air inlet but lower than the lower edge of the exhaust port, so that the vertical section completely covers the furnace wall between the upper edge of the air inlet and the lower edge of the exhaust port; the outlet end of the horizontal section is lower than the lower edge of the exhaust port, with an inclination angle α=45°.
7. The chemical vapor deposition apparatus according to claim 6, characterized in that, The inner wall of the furnace body is integrally formed with a streamlined cross-section annular support platform at a corresponding height. The upper end of the vertical section is provided with an outward flange, which is placed and fixed on the upper surface of the annular support platform. The radial protrusion width of the annular support platform is 15mm-25mm, and its windward and leeward sides are both arc-transitioned guide slopes.
8. The chemical vapor deposition apparatus according to claim 7, characterized in that, The height of the annular support platform is 10mm-20mm, its lower end face is higher than the upper edge of the air inlet, and its upper end face is lower than the lower edge of the exhaust port; within the height range of the annular support platform, the radial width of the flow guide channel is 15mm-25mm; above and below the annular support platform, the radial width of the flow guide channel is maintained at 30mm-50mm.
9. The chemical vapor deposition apparatus according to claim 7, characterized in that, The outward-facing flange has 16-32 vent holes evenly distributed along its circumference, and the total flow area of the vent holes is not less than 80% of the cross-sectional area of the flow guide channel; or, the outward-facing flange is a segmented structure, consisting of multiple independent flange lugs arranged at intervals along its circumference, with the gaps between adjacent lugs serving as airflow channels.
10. The chemical vapor deposition apparatus according to claim 5, characterized in that, The diameter of the disc-shaped crucible bottom is 600mm and the thickness is 30mm; the inner diameter of the cylindrical crucible wall is 610mm and the height is 300mm; the width of the annular gap is 5mm-10mm; the connecting rod passes through the central opening of the annular rotating platform, and a dynamic sealing bearing is provided between the two.
Citation Information
Patent Citations
Large-size high-uniformity synthetic quartz glass ingot deposition furnace and preparation method
CN117776505A
A method for synthesizing large-size quartz glass by multi-burner CVD
CN118954913B
Deposition furnace for manufacturing large-size high-uniformity synthetic quartz glass and preparation method of large-size high-uniformity synthetic quartz glass
CN118993508A
Quartz glass member and projection aligner
CN1226212C
Synthetic silica glass member, photolithography apparatus and process for producing photolithography apparatus
CN1657456A